Association between hedonic hunger and body mass index in adults: A systematic review and meta-analysis - Karamizadeh, Malihe; Akbarzadeh, Marzieh; Pourghassem Gargari, Bahram; Mahdavi, Reza; Nikniaz, Zeinab (Appetite, 2024)
Hedonic hunger has been proposed as one of the important causes of obesity in recent years. In the present study, we systematically reviewed and meta-analyzed the relationship between hedonic hunger and body mass index (BMI) in healthy adults. PubMed, Web of Science, and Scopus were searched until January 19, 2023. All English-language original observational studies conducted on healthy adult subjects, which used the Power of Food Scale (PFS) to evaluate hedonic hunger were included. Quality assessment was done using the Joanna Briggs Institute checklist, and StataMP-17 software was used for the meta-analysis. After screening, 25 observational studies with a total of 14457 participants were included. Twenty-four studies were cross-sectional, and one was a cohort study. Twenty-two studies examined both sexes, two studies were conducted only on women, and one study conducted analysis separately on men and women. The results of the meta-analysis showed a positive and significant association between hedonic hunger and BMI with a small effect size (r = 0.13, 95% CI: 0.08, 0.18). In addition, a positive significant association was observed between subscales of PFS (“food available”, “food present”, and “food tasted”) and BMI. The association between hedonic hunger and BMI was not affected by the results of meta-regression analysis of %female, mean age & BMI, and sample size. In conclusion, there was a positive significant association between hedonic hunger and BMI, but the effect size was weak. Considering the low quality of included studies, we need longitudinal design studies considering the association between these two variables as a primary outcome for a more accurate conclusion.